FC 057SALIVARY POTASSIUM FOLLOWS PLASMA POTASSIUM DYNAMICS IN HEMODIALYSIS PATIENTS. (29th May 2021) - Deak, Andras; Belić, Katarina; Meissl, Anna-Maria; Artinger, Katharina; Eller, Kathrin; Rechberger, Bernd; Niedrist, Tobias; Graier, Wolfgang; Malli, Roland; Bischof, Helmut; Burgstaller, Sandra; Avian, Alexander; et al.
Abstract: Background and Aims: Hyperkalemia is common in patients on hemodialysis (HD) and in cardiorenal patients on RAAS inhibitors. Frequently, hyperkalemia is a leading reason to withdraw potentially lifesaving therapy in cardiorenal patients. Out-patient monitoring of plasma K + levels due to preanalytical problems has proven problematic. The present pilot-study examined salivary K + levels and kinetics based on plasma K + measurements in HD patients employing a novel class of genetically-encoded fluorescent potassium-ion indicators, the GEPIIs (Bischof et al. Nat. Commun. 2017) . HD patients represent a unique population in whom significant K + derangements and rapid K + level changes predictably occur and where these phenomena can be safely investigated. Method: K + assessments were performed in healthy individuals (n=20) and HD patients (n=30). Study-related procedures were approved by the local Institutional Review Board. Healthy individuals were recruited on a voluntary basis and provided only saliva samples. HD patients were recruited from our HD unit. Blood and saliva samples for K + assessment were collected simultaneously during three consecutive HD sessions (HD1-3) prior to and directly after each session (pre/post HD). Blood was drawn in a standardized procedure directly from the HD access line and plasma K + was measured immediately using standardized ion-selective electrodes (ISE). Saliva samples were gathered in a standardized procedure using a commercially available collection device (SuperSAL TM ). Of note, gaining adequate amounts of saliva from chronic HD patients, who frequently suffer from xerostomia, has proven challenging in some cases. The K + content of saliva samples was measured by ISE and GEPII-technique. For the latter, samples were mixed with purified GEPIIs and were inserted into a fluorescent plate-reader. Probes were illuminated at 430 nm and emission light were collected at 475 nm and 525 nm, respectively. The ratio of the fluorescent intensities (F535 /F480 ) after appropriate calibration is a direct measure of the K + concentration sensed by GEPIIs. Results: K + determination in saliva samples using the GEPII-technique and ISE showed a strong agreement ((Figure 1A ), Bias 0, 71; 95% limits of agreement from -2.79 to 4.40). Pre-dialytic [K + ]saliva of HD patients compared to healthy individuals, was higher (40, 64±1, 50 vs. 23, 15±0, 76 mmol/l, p<0.05). As expected, each HD session (HD1-3) led to a significant reduction in [K + ]plasma, which is followed by a similar, significant reduction of [K + ]saliva (Figure 1B ). Dynamics of plasma and salivary [K + ] showed a very similar pattern: strong reduction during a HD session followed by a marked increase in the dialysis-free period until the next session 48-72h later (Figure 1C ). Although basal [K + ]saliva shows individual variations, [K + ]Saliva and [K + ]plasma exhibited a tendency of linear association (Figure 1D ). Correlation analysis in each HD session (HD1-3 pre/post) revealed however no or weak correlation of pre- and post-dialytic saliva and plasma K + values (Figure 1E ). Conclusion: The GEPII-technique is an easy to use, reliable and suitable method for salivary K + determination in healthy individuals and in HD patients with accuracy and precision comparable to that of ISE. Despite heterogeneous baselines, changes of [K + ]saliva represent a sensitive marker of K + derangements as well as hyper- and normokalemia in HD patients. Although we observed that [K + ]saliva dynamically follows [K + ]plasma, an exact quantification - most likely due to the low number of cases per HD sessions in this pilot-study – was not possible. Additionally, how closely [K + ]saliva tracks [K + ]plasma in patients with hypokalemia was not addressed in this study. To confidently answer whether [K + ]saliva measurement can potentially be used in the care of patients at increased risk of hyperkalemia, further studies in a larger number of patients need to be conducted.